Application of bonebed-malleus short process registration in minimally invasive cochlear implantation. (16th December 2016) - Ke, Jia; Zhang, Shaoxing; Li, Changsheng; Zhu, Yunfeng; Hu, Lei; Ma, Furong
Abstract: Purpose: This article proposed and investigated the application of bonebed-malleus short process registration in minimally invasive cochlear implantation, and assessed the value of the proposed strategy for image-guided otologic surgery. Materials and methods: Ten temporal bone specimens were marked with both shallow and deep targets in order to measure registration resolutions. Two registration methods were applied. Method A (a new registration method) consisted of bonebed-malleus short process registration, while method B (traditional registration method) comprised registration using four titanium screws attached at the mastoid surface. The target registration errors (TRE) were measured at both the shallow and deep fiducial targets. After registration achieved by method A, percutaneous cochlear drilling was conducted on the other eight temporal bone specimens in order to observe the deviation from the target point and entry point. Results: Using method A, the error observed at the shallow fiducial markers of specimens was less than 1 mm, while the error observed at the deep fiducial markers was approximately equal to 1 mm. No significant difference was observed when results were compared with the application of method B. In eight studied cases using method A, drilling operations were successfully conducted. The deviations from the target point and the entry point were 0.84 ± 0.30 and 0.66 ± 0.51 mm, respectively. Conclusions: Results of the present study indicated that the new registration method demonstrated identical accuracy when compared to traditional registration method, achieved less invasiveness. Thus, the proposed method might be a feasible registration method for image-guided otologic surgery due to its mild invasiveness and high accuracy.